2016
DOI: 10.1515/reveh-2016-0026
|View full text |Cite
|
Sign up to set email alerts
|

A review of heavy metals in indoor dust and its human health-risk implications

Abstract: Indoor dust acts as a media for heavy metal deposition. Past studies have shown that heavy metal concentration in indoor dust is affected by local human activities and atmospheric transport can have harmful effects on human health. Additionally, children are more sensitive to heavy metals due to their hand-to-mouth behaviour and rapid body development. However, limited information on health risks were found in past dust studies as these studies aimed to identify heavy metal concentrations and sources of indoor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(69 citation statements)
references
References 40 publications
1
50
1
3
Order By: Relevance
“…Previous studies have indicated that areas in the vicinity of urban and industrial sites are characterized by higher metal concentration in indoor dust, compared to rural and village ones. The metal concentration in indoor dust was altered by the building's dustiness and ventilation pattern (Tan et al, 2016).…”
Section: Indoor To Outdoor Relationshipmentioning
confidence: 99%
“…Previous studies have indicated that areas in the vicinity of urban and industrial sites are characterized by higher metal concentration in indoor dust, compared to rural and village ones. The metal concentration in indoor dust was altered by the building's dustiness and ventilation pattern (Tan et al, 2016).…”
Section: Indoor To Outdoor Relationshipmentioning
confidence: 99%
“…Recent reports highlighted the potential health-related concerns associated with dust particle exposure, 3 in particular in areas close to industrial sites where higher heavy metal concentration in indoor dust has been reported. 4 Multidisciplinary reports about indoor measurements in heavily polluted areas on health-relevant chemical and physical properties are still scanty. 5 In addition to the specific sources related to indoor activities, indoor air quality (IAQ) has been shown to have a direct association with the quality of outdoor air 6 ; the contribution due to the infiltration of pollutants from outdoor sources has been analyzed in some previous studies, some of which focused on particulate matter (PM).…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals in case of their non-degradable properties can have high toxicity and adverse effects on health [11,12]. Ingestion, inhalation and dermal contact are the ways of taking heavy metals in to human body [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%